2017
DOI: 10.2134/jeq2017.04.0158
|View full text |Cite
|
Sign up to set email alerts
|

Cropping System and Type of Pig Manure Affect Nitrate‐Nitrogen Leaching in a Sandy Loam Soil

Abstract: The application of livestock manure can result in the loss of nitrate-nitrogen (NO-N) and degrade surface and groundwater. A 3-yr lysimeter study was set up to compare the effect of cropping system and nitrogen (N)- and phosphorus (P)-based pig manure application rates on the loss of water and NO-N below the root zone. The experiment was a split-plot design with annual and perennial cropping systems as the main factor. Five nutrient management treatments were the subplots: N-based liquid pig manure application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
2
14
1
Order By: Relevance
“…The total NO 3 − -N leached from the control plots was 21 and 19 kg ha −1 in 2010 and 2011, respectively, suggesting that although NO 3 − -N leaching can be reduced by withholding supplemental N, it may be unavoidable, particularly in sandy soils. Similarly, the lysimeter results of Karimi et al (2017) showed that the amount of NO 3 − -N lost below the root zone of an annual crop at Carman, MB, was 24 to 48 kg N ha −1 from unfertilized control plots.…”
Section: Nitrate Leachingmentioning
confidence: 86%
See 1 more Smart Citation
“…The total NO 3 − -N leached from the control plots was 21 and 19 kg ha −1 in 2010 and 2011, respectively, suggesting that although NO 3 − -N leaching can be reduced by withholding supplemental N, it may be unavoidable, particularly in sandy soils. Similarly, the lysimeter results of Karimi et al (2017) showed that the amount of NO 3 − -N lost below the root zone of an annual crop at Carman, MB, was 24 to 48 kg N ha −1 from unfertilized control plots.…”
Section: Nitrate Leachingmentioning
confidence: 86%
“…One field core lysimeter was installed along the centerline of each plot, 2 m from the southern edge, to measure water and NO 3 − – N moving below the rooting zone (Nikièma et al, 2013). The lysimeters consisted of three parts (Karimi et al, 2017): the main column, a schedule 80 polyvinyl chloride (PVC) pipe (54‐cm i.d., 106‐cm length) representing the root zone of annual crops, a circular perforated plate, and a bottom cap for collection.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, N removal from the solid-N plot was not statistically different from the control, again indicating low N availability in the solid manure. The leachate results obtained using field core lysimeters in these study plots also showed that this treatment reduced the risk of nitrate leaching, likely due to immobilization of N with the addition of straw in the manure (Karimi et al 2017). Previous studies have shown that the formula used in Manitoba to estimate available N in manure (available N in manure = 75% of NH + 4 -N + 25% of organic N) does not account for the effect of a relatively high C:N ratio (11-14, Loecke et al 2004) of the solid manure on N release and overestimates N availability for solid manures (Ige et al 2015).…”
Section: Perennial Yield and Nutrient Removalmentioning
confidence: 57%
“…It would take time for the mineralization of organic N to ammonium, and depending on the C:N ratio of the manure, immobilization of N may have also occurred. In addition, the leachate results obtained in these plots showed that solid manure reduced the risk of nitrate leaching (Karimi et al 2017). Therefore, it is likely that the method used to estimate available N from organic N in the solid manure overestimated the quantity of N mineralized.…”
Section: Aboveground Biomass Apparent N and P Recoverymentioning
confidence: 93%
See 1 more Smart Citation